Design and Implementation Oxygen Sensor Used Graphene Metal Nanocomposites by LIFT Method - Kadom, Ala'a Hameed; Hachim, Ahmed Sameer; Neamah, Tiba Laiq; Sattar, Hadeel Qasim; Mahdi, Waleed Sabah (American Journal of Biodiversity, 2025)
Nanoparticles aroused great interest. In this study, a gas sensor (oxygen sensor) was fabricated using Laser-induced forward transferuses with nanomaterials (grapheneGO - nanosilver Ag- titanium dioxideTiO2) Where the nanomaterials were diagnosed using a (Filed Emission scanning electron microscopy FE-SEM) and the materials were within the nanoscale, the sensor was used to measure the gases in the room, as well as the leakage of gases in the gas systems and others.